EFFECTIVENESS OF INDIVIDUALIZED NUTRITIONAL AND VITAMIN-MINERAL CORRECTION IN THE PREVENTION OF METABOLIC COMPLICATIONS AFTER BARIATRIC SURGERY - B.M. Iminov; Sh.N. Kadirov; B.U. Iriskulov (Journal of modern medicine, 2026)
Bariatric surgery provides a substantial and sustained reduction in body weight and contributes to the improvement of obesity-related metabolic disorders. However, anatomical and functional changes in the gastrointestinal tract, restriction of food intake, and disturbances in digestion and nutrient absorption may lead to protein-energy deficiency, anemia, vitamin and mineral deficiencies, as well as disorders of bone metabolism. Therefore, the long-term success of bariatric surgery depends not only on weight loss but also on maintaining adequate nutritional and metabolic status in the patient. The aim of this study was to assess the effectiveness of an individualized approach to nutritional correction and vitamin-mineral supplementation in preventing metabolic complications after bariatric surgery. The personalized program includes a comprehensive assessment of the patient’s baseline nutritional status, type of surgical procedure, changes in body weight, dietary habits, parameters of protein and mineral metabolism, as well as serum levels of iron, ferritin, vitamin B₁₂, folate, vitamin D, calcium, magnesium, zinc, and other essential micronutrients. Individual selection of nutritional support based on the identified deficiencies and the patient’s metabolic characteristics makes it possible to correct abnormalities that arise at different stages of the postoperative period in a timely manner. Regular laboratory monitoring is particularly important because early stages of micronutrient deficiency often develop before obvious clinical manifestations become apparent. A personalized preventive strategy allows nutritional correction to be regarded not as an additional component of surgical treatment, but as an integral part of long-term patient management. A comprehensive approach combining balanced nutrition, targeted protein support, correction of vitamin and mineral deficiencies, and regular laboratory monitoring helps reduce the risk of late metabolic complications, preserve the functional capacity of the body, and improve the long-term effectiveness of bariatric treatment.